Perceived Self-Efficacy, Confidence, and Skill Among Factors of Adult Patient Participation in Transitional Care: A Systematic Review of Quantitative Studies - Andrea Bailey MSN, RN, FNP-BC; Jennifer Mallow PhD, RN, FNP-BC; Laurie Theeke PhD, FNP-BC (SAGE Publishing, 2022)
Introduction An advancing healthcare system in which patients are often required to self-manage care needs across countless settings and clinicians is increasing focus on participation in care. Mismanagement of care during already risky care-transitions further increases adverse care outcomes. Understanding factors of patient participation in transitional care in an adult population can help guide ways to reduce this burden. Methods A systematic review of the literature guided by the PRISMA method was conducted to identify factors of patient participation in transitional care. Quantitative studies in which patient participation was measured as an outcome variable and related statistics reported, and data were collected from an adult sample, were included. Two authors independently reviewed, critiqued, and synthesized the articles, and later categorized study variables according to identified trends. Results Twelve studies across international and multidisciplinary backgrounds were identified. Across studies, efforts were largely based on understanding or improving patient self-management of care during transitions. The majority of studies were experimental and care interventions grounded in patient and healthcare team partnerships, delivered beyond the hospital setting. An array of measures was used to quantify patient participation. Factors of patient participation in transitional care included higher perceived levels of self-efficacy, confidence, and skills to participate in care. Conclusion The results of this study suggest patient participation in transitional care is largely based on perceptions of self-efficacy, confidence, and skill. Patient-centric transitional care interventions targeting these factors and delivered beyond the hospital setting may improve care outcomes. Implications and direction for further studies includes conceptual clarity, the study of a broader-reaching patient population demographic, and use of multidisciplinary interventions. Outcome variables should remain focused on patient perception of care involvement and participation and expanded to include variables such as functional abilities and social determinants of health.